PERAN PEMERINTAH DAERAH KABUPATEN BANDUNG DALAM TANGGAP BENCANA COVID-19 (Institut Pemerintahan Dalam Negeri, 2021)
Corona Virus Disease 19 or abbreviated as COVID 19 has been a disaster for the world since 2019. COVID 19 originating from Wuhan, China has claimed many victims and damaged the order in all aspects of life ranging from economic, political, social, to government aspects. The central and regional governments have the most important role in handling COVID-19. All stakeholders, both at the central and regional levels, must increase their hard work in a more coordinated and integrated manner so that the impact of COVID-19 can be minimized and even an antidote can be found. Based on this, researchers are encouraged to try to describe and describe the role of the Bandung Regency government which is considered relatively successful in tackling disasters caused by the COVID-19 pandemic, this study uses a qualitative research approach with descriptive methods based on facts and data obtained. As a result, the role of the Bandung Regency Government is very important in handling Covid 19, this is evidenced by several policies and regulations launched by the Bandung Regency Government that can minimize the spread of the Covid 19 virus. has been issued. Key Words: Role, Bandung District Government, And The Covid-19 Pandemic